Sosialisasi Teknologi Desalinasi Sederhana di Pesisir Kabupaten Karawang - Sewiko, Roni; Herlina Adelina Meria Uli Sagala; Aris Kabul; Roberto Patar Pasaribu (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Provision of clean water for the community is still a big problem in Indonesia. To overcome this, it is necessary to make an alternative efforts to obtain water that is suitable for use. This community service activity aims to introduce a simple technology to obtain useable water by applying simple desalination technology. This activity was carried out by the Department of Marine Engineering, Karawang Marine and Fisheries Polytechnic. This program has been carried out in Tambak Sari Village, Tirtajaya District, Karawang Regency, West Java. The method is carried out by counseling and direct demonstrations in the field. The community service program planned by the lecturers of the Marine Engineering Study Program, KP Karawang Polytechnic can be carried out well. This happened because of good cooperation and supported by the Director of Polytechnic, the Head of Tambak Sari Village and the surrounding stakeholders and Community Groups.